Compiler-compiler for an eight bit microprocessor - Kasmiran Jumari,; K.R. Dimond, (1991)
This paper shows the technique that can be used to design a compiler-compiler for an eight bit microprocessor. Using the translated parser which is the same in every application program, the task of designing application dependent programs is greatly eased. Of particular interest is the power of a Yet Another Compiler-Compiler (YACC) can now be appreciated by the microprocessor based designer